Pengembangan Media Pop Up Book Bermuatan Ejaan Suku Kata untuk Meningkatkan Kemampuan Membaca Permulaan Siswa Kelas I SD - Junita Asih; Suryandari Suryandari; Galih Albarra Shidiq; Indah Perdana Sari (Alma Ata University Press, 2025)
This study aims to develop Pop-up Book learning media featuring syllable spelling to enhance the beginning reading skills of first-grade elementary school students. Beginning reading skills are a crucial foundation for young learners to recognize letters, spell words, and read simple sentences. The research employed the Research and Development (R&D) method with the Borg and Gall model, encompassing stages such as needs analysis, product development, initial trials, evaluation, and revision. The study was conducted with first-grade students from SD Muhammadiyah Kalakijo, utilizing data collection techniques including material, media, and teacher validation questionnaires, student interviews, and baikobservations of reading progress after using the media. The results indicated that the media was deemed appropriate, with a material expert validation score of 75% and a media expert validation score of 87.5%. Teacher responses were highly favorable, with a 100% agreement on the media’s effectiveness in supporting learning activities. Students provided positive feedback, describing the Pop-up Book as engaging, easy to use, and enjoyable, significantly improving their beginning reading abilities. This media not only enhances students' reading skills but also motivates them to learn with enthusiasm. The study demonstrates that visually appealing and interactive Pop-up Books can serve as innovative and effective tools for teaching reading. The use of syllable spelling further facilitates students in gradually understanding the material. It is hoped that this media development can be widely implemented in various educational settings to support literacy needs among young learners.